Profile of Creative Thinking Skill of New Normal Era at Junior High School Students - Almuharomah, Farida Amrul; Sunarno, Widha; Masykuri, Mohammad (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The demands of teachers to train 21st century skills are very challenging, especially in the current pandemic era. This study aims to determine the creative thinking ability of junior high school students in Ponorogo district. Quantitative descriptive is used as a research method. The population used is a junior high school in Ponorogo district. The sample was taken as many as one class in each school. the achievement of creative thinking indicators on average is 33.5% in the less category. Analysis of fluency indicators is 35%, flexibility is 32%, originality is 39%, and elaboration is 28%. The achievement of 4 indicators of creative thinking is in the less category. Students creative thinking ability level of in the creative category of 2.88%, and the non-creative category is 19.42%. Students at the creative level are at SMPN 1 Mlarak by 20% and at SMPN 1 Kauman by 3.33%. Creative thinking skills can be trained through learning including always doing apperception before starting learning, using project-based learning models, or using STEM-based learning approaches.